A Miniaturized Percoll Gradient Method for Isolation of Quiescent Cells of Yeast - Cenxuan Zu; Jia Dong; Yue Zhang; Yao Zhang; Zongzheng Huang; Shaolan Zou (Bio-Protocol)
Quiescence, the temporary and reversible exit from proliferative growth, is a fundamental biological process. Budding yeast is a preeminent model for studying cellular quiescence owing to its rich experimental toolboxes and evolutionary conservation across eukaryotic pathways and processes that control quiescence. Yeast quiescent cells are reported to be isolated by the continuous linear Percoll gradient method and identified by combining different features such as cell cycle, heat resistance, and cell morphology (single cell). Generally, 10–25 mL of Percoll isotonic solution is first obtained by mixing Percoll with NaCl in 12.5–30 mL centrifugal tubes. Then, the gradient is prepared at high speed for 15–60 min. Finally, approximately 2 × 109 cells are collected, overlaid onto the preformed gradient, and centrifuged to obtain distinct cell fractions. This method requires more reagents and samples and special centrifuges and centrifuge tubes. Besides the cost, it is less favorable for experiments that require high-throughput analyses with a small volume of sample each time. The protocol described here aims to solve those problems by combining the use of 2 mL centrifugal tubes with density marker beads. The protocol also focuses on how to optimize the buoyant density distribution of the density gradient solution such that the density bands better match those of different fraction cells. This will help fully separate quiescent and non-quiescent cells. The protocol can be easily adapted to a wide variety of unicellular microbes with different buoyancy density differentiation during cultivation, such as yeast and bacteria.